Rambutan genome revealed gene networks for spine formation and aril development. (13th October 2021) - Zhang, Wenping; Lin, Jishan; Li, Jianguo; Zheng, Shaoquan; Zhang, Xingtan; Chen, Shuai; Ma, Xiaokai; Dong, Fei; Jia, Haifeng; Xu, Xiuming; Yang, Ziqin; Ma, Panpan; et al.
SUMMARY: Rambutan is a popular tropical fruit known for its exotic appearance, has long flexible spines on shells, extraordinary aril growth, desirable nutrition, and a favorable taste. The genome of an elite rambutan cultivar Baoyan 7 was assembled into 328 Mb in 16 pseudo‐chromosomes. Comparative genomics analysis between rambutan and lychee revealed that rambutan chromosomes 8 and 12 are collinear with lychee chromosome 1, which resulted in a chromosome fission event in rambutan ( n = 16) or a fusion event in lychee ( n = 15) after their divergence from a common ancestor 15.7 million years ago. Root development genes played a crucial role in spine development, such as endoplasmic reticulum pathway genes, jasmonic acid response genes, vascular bundle development genes, and K + transport genes. Aril development was regulated by D‐class genes ( STK and SHP1 ), plant hormone and phenylpropanoid biosynthesis genes, and sugar metabolism genes. The lower rate of male sterility of hermaphroditic flowers appears to be regulated by MYB24 . Population genomic analyses revealed genes in selective sweeps during domestication that are related to fruit morphology and environment stress response. These findings enhance our understanding of spine and aril development and provide genomic resources for rambutan improvement. Significance Statement: Rambutan genome revealed a chromosomal fission or fusion event causing karyotype variation between rambutan and lychee. Root development genes played a crucial role in spine development, including endoplasmic reticulum pathway, jasmonic acid response, vascular bundle development, and K + transport genes.